After the Deluge: New Perspectives on the Intellectual and Cultural History of Postwar France - Bourg, Julian (Lexington Books, 2004)
Madame de Pompadour's famous quip, 'Apr_s nous, le deluge,' serves as fitting inspiration for this lively discussion of postwar French intellectual and cultural life. Over the past thirty years, North American and European scholarship has been significantly transformed by the absorption of poststructuralist and postmodernist theories from French thinkers. But Julian Bourg's seamlessly edited volume proves that, historically speaking, French intellecutal and cultural life since World War Two has involved much more than a few infamous figures and concepts. Motivated by a desire to narrate and contextualize the deluge of 'French theory,' After the Deluge showcases recent work by today's brightest scholars of French intellectual history that historicizes key debates, figures, and turning points in the postwar era of French thought. Relying on primary and archival sources, contributors examine, among other themes: left-wing critiques of the Left, the internationalizing of thought, the institutional and affective conditions of cultural life, and the religious imagination. They revive neglected debates and figures, and they explore the larger impact of political quarrels. In an afterword, preeminent French historian Fran_ois Dosse heralds the arrival of a new generation, a historiographical sensibility that brings fresh, original perspectives and a passion for French history to the contemporary French intellectual arena. After the Deluge adds significant depth and breadth to our understanding of postwar French intellectual and cultural history.